Recurrent Anaplastic Meningioma with Metastasis - Uzma Saeed, Naveed Mazhar, Zeeshan Saeed (Pakistan Journal of Medical & Health Sciences, 2023)
Meningioma is the commonest primary brain tumor in adults, constituting 30% of all intracranial tumors. 1-3 These arise from arachnoid cap cells located in arachnoid villi. The majority of meningiomas originate from brain meninges, but 10% of all cases originate from spinal cord meninges. 4 There are 3 subtypes of meningioma according to World Health Organization (WHO). WHO Grade 1, benign meningioma making approximately 90% of all meningiomas. WHO Grade 2, atypical meningioma represents 5-7% and WHO Grade 3, anaplastic, or malignant meningioma represent 1-3%. 1,2 Grade 3 meningiomas behave aggressively with the worst prognosis. They have a high local recurrence rate and rarely develop distant metastasis. 4,5 As extracranial metastasis is extremely rare, seen in less than 0.1-0.2 % of all meningiomas, 2,3 a high index of suspicion should be kept when encountered with such lesions in patients with recurrent atypical/anaplastic meningiomas.